Challenges in translating English wordplays into Indonesian: An annotated translation of Paperboy novel by Vince Vawter - Adani Nur Sabrina (Universitas Merdeka Malang, 2024)
Wordplays are fun and pleasurable, yet challenging for translators. The researcher translated the Paperboy novel by Vince Vawter and found many wordplays in it. In this research, the researcher aims to find the various wordplays contained in the novel, determine at what level of language the wordplays are, classify the wordplay into the appropriate taxonomy, and find out the most suitable translation strategy for each wordplay. The methods used are introspective and retrospective. The results of this research show that there are 26 data of wordplays that cover 3 lexical plays, 19 sound plays, and 4 visual plays. In terms of taxonomy, those data cover 7 homonyms, 7 paronyms, 5 malapropisms, 6 rhymes, and 1 eggcorn. The translation strategies used are 19 wordplay to wordplay, 3 wordplay ST to wordplay TT, 1 wordplay to non-wordplay, 1 non-wordplay to wordplay, and 2 editorial techniques. Based on the most used translation strategies, i.e. wordplay to wordplay, it can be seen that even though wordplays are challenging, they are not totally impossible to translate.